Demystifying China: new understandings of Chinese history - Standen, Naomi (Rowman & Littlefield, 2013)
Notes on Romanization, Names, and Chinese Characters -- Introduction: The Creation of History in China / Naomi Standen -- Part I. Images of an Ancient and United Nation -- The Chinese / Peter C. Perdue -- The Great Wall / Peter Lorge -- Foreign Conquerors of China / Naomi Standen -- Confucius : The Key to Understanding China / Tim Barrett -- Part II. Cultural Traditions -- The "Decline" of Buddhism in China / Tansen Sen -- Islam in China / Michael Brose -- Chinese Medicine / Bridie Andrews -- Traditional Chinese and the Environment / Ling Zhang -- Chinese Martial Arts / Stanley E. Henning -- Women in Chinese History / Clara Wing-chung Ho -- Part III. Imperial China -- China's Age of Seafaring / Ruth Mostern -- Civil Service Examinations / Elif Akcetin -- Modern China's Borders / Andres Rodriguez -- Xinjiang at the Center / Judd Kinzley -- Tibet / Elliott Sperling -- The Opium War and China's "Century of Humiliation" / Julia Lovell -- Part IV. Making Modern China -- Sun Yat-sen / Wasana Wongsurawat -- Republican China under the Nationalists, ca. 1925-1945 / Felix Boecking -- The Rise of the Chinese Communist Party / Christian Hess -- Simplified Characters / Imre Galambos -- The One-Child Policy / Barbara Mittler -- The Cultural Revolution, 1966-1976 / Marjorie Dryburgh -- China's Political System / Hai Ren -- Tiananmen 1989 / Fabio Lanza
Includes bibliographical references and index
Keywords: China -- History; China -- History -- Errors, inventions, etc; China -- Civilization; China -- Politics and government; Aufsatzsammlung; Chinabild; Geschichtsschreibung